KEMAMPUAN PEMECAHAN MASALAH BERDASARKAN PEMAHAMAN KONSEPTUAL SISWA MATERI OPERASI BILANGAN RASIONAL - Mawazi Mawazi; Zubaidah Zubaidah; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstrackThe research aims to describe the problem solving ability based on student conceptual understanding of rational number operations in ten grade SMK  Negeri 2 Pontianak. The method is used descriptive method with survey of research. The sample of research was 9 studens. The sample determination is done by taking 3 students who have high conceptual understanding, 3 students who have average conceptual understanding, and 3 students who have low conceptual understanding. The result of data analysis showed that  students who have high conceptual understanding have very good problem solving ability, students who have average conceptual understanding have good problem solving ability, and students who have low conceptual understanding have bad problem solving ability.Keywords: Problem Solving Ability, Conceptual Understanding, Rational Number Operations